Resource of Received Knowlodge upon the Contemporary Imamiyyah Shia and Its Correlation with the Classical Scholars| مصدر التلقي المعرفي لدى الشيعة الإمامية المعاصرين وعلاقته بالقدامي - Kholid Muslih (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2014)
Unlike the other sects, especially the Ahlussunah, Twelver Shia or the Imamiyyah havestructure as well as a unique source of knowledge; where they believe that those oftwelve Imams are as an authentic source of knowledge other than Allah and Hismessenger. Whole words, actions and decisions of the Prophet and those Imams werecodified by the authors in a book known as